Scientists and software – surveying the species distribution modelling community. Issue 3 (20th January 2015) - Ahmed, Sadia E.; McInerny, Greg; O'Hara, Kenton; Harper, Richard; Salido, Lara; Emmott, Stephen; Joppa, Lucas N.; Elith, Jane
Abstract Aim Software use is ubiquitous in the species distribution modelling (SDM) domain; nearly every scientist working on SDM either uses or develops specialist SDM software; however, little is formally known about the prevalence or preference of one software over another. We seek to provide, for the first time, a 'snapshot' of SDM users, the methods they use and the questions they answer. Location Global. Methods We conducted a survey of over 300 SDM scientists to capture a snapshot of the community and used an extensive literature search of SDM papers in order to investigate the characteristics of the SDM community and its interactions with software developers in terms of co‐authoring research publications. Results Our results show that those members of the community who develop software and who are directly connected with developers are among the most highly connected and published authors in the field. We further show that the two most popular softwares for SDM lie at opposite ends of the 'use‐complexity' continuum. Main conclusion Given the importance of SDM research in a changing environment, with its increasing use in the policy domain, it is vital to be aware of what software and methodologies are being implemented. Here, we present a snapshot of the SDM community, the software and the methods being used.